Frida the wondercat - Everitt, Betsy (San Diego : Harcourt Brace Jovanovich, 1990)
Louise and her cat, Frida, find on their doorstep a magical collar which changes their lives.
School Library Journal.
Booklist.
Horn Book.
2.7
K-3
Keywords: Cats -- Fiction; Magic -- Fiction; Cats -- Fiction; Magic -- Fiction; Cats -- Fiction; Magic -- Fiction